Floral Development Reveals the Existence of a Fifth Staminode on the Labellum of Basal Globbeae - Iwamoto, Akitoshi; Ishigooka, Shiori; Cao, Limin; Ronse De Craene, Louis P. (Frontiers in Ecology and Evolution, 2020)
We observed the floral development of Hemiorchis burmanica and two species of Gagnepainia, which make up the sister group of Globba in Globbeae, as well as a selected number of species of Globba. Our observations revealed that in Gagnepainia a “fifth staminode” develops as part of the labellum, while it is generally lost in other Zingiberaceae. The fifth staminode, however, was not initiated in the labellum of Hemiorchis. A fifth staminode was also observed in Globba geoffrayi, but was not found in all other species of Globba investigated. While the staminode becomes integral part of the labellum in Gagnepainia, it remains small and almost aborts at later stages of development in Globba geoffrayi. These results indicate that the development of a fifth staminode could be a recurring plesiomorphic trait for Globbeae, only retained in G. geoffrayi. The retention of the fifth staminode and its heterochronic shift may be linked with the mechanical constriction within the flower bud. The results may also support the interpretation of an atavistic expression of a once lost staminode.